PENDIDIKAN JASMANI DAN KESEHATAN DALAM PERSPEKTIF AL QUR’AN - Baiq Siti Hajar; Lalu Moh Yudha Isnaini (Pascasarjana Universitas PTIQ Jakarta, 2023)
The physical structure will not be able to form an outward behavior, and vice versa the spirit will not function if there is no body as a vessel for the spirit. These two things reflect that humans are the noblest and most beautiful creatures compared to other creatures created by Allah SWT. Health includes physical and spiritual. The aim of the research is to find out the Physical Education of sport and health in the Al-Qur'an. The research method uses a qualitative descriptive study of the verses of the Koran which have the intention of physical education, sports and health. The data source of this research uses secondary and primary data. Methods of data collection using the method of content analysis and manuscript review. Data analysis techniques used content analysis and literature review. The results of the research are exercise and rest in the Qur'an namely Al-Furqan: 47, Al-Qashahs: 73, An-Naba': 9, Ar-Rum: 23). Furthermore, regulate diet and health (Al-A'raf: 31, Al-Mukmin: 43, Al-Maidah: 5). The verses of the Qur'an in Sports Physical Education and Health in the World of Education are understood in the context of events and to give attention in the context of self-effort to worship Allah